Rape Victim Suffering from Mental Retardation and Psychosis: MTP Allowed Without Consent: Kerala High Court (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
The victim was found wandering within the limits of Kazhakoottam Police Station and was taken by the Police initially to a psycho-social rehabilitation centre and then to the Mental Health Centre, Peroorkada. The Medical Board at the Mental Health Centre found the victim to be pregnant, having gestation period corresponding to eight weeks as on 4.6.2021 [Para 2]. Certificate issued by the Medical Board attached to the Mental Health Centre, Peroorkada indicates that the victim is suffering from mental retardation with psychosis and is under treatment as inpatient. It is recited in the said Certificate that the victim is unable to take decision or communicate her opinion. Kerala High Court concluded that reverting to the facts, having regard to the fact that the person involved in the case is a rape victim and considering the opinion of the Medical Board, that in a case of this nature, it is in the best interests of the person concerned to permit termination of her pregnancy. In the result, the writ petition was allowed and respondents 5 and 6 were permitted to terminate the pregnancy of the victim involved in this matter at the earliest in accordance with the provisions of the MTP Act, without insisting on the consent of the victim. Having regard to the fact that the person is a rape victim, there was also a direction to respondents 5 and 6 to take the tissue of the fetus and maintain the same for DNA examination.
Keywords: MTP act; Consent; Consent Mental retardation; Psychosis; Rape victim; Medical board; Doctrine of parens patirae; DNA examination; Test of best interests of the person; Psycho-social rehabilitation centre; Mental health centre